How the COVID-19 pandemic affected young people’s mental health and wellbeing in the UK: a qualitative study - Waite, P; Pearcey, S; Burgess, L; Shum, A; Sajid, E; Millie, S; Klampe, M-L; Lawrence, PJ (SAGE Publications, 2023)
There is emerging evidence of the detrimental impact of the pandemic and associated restrictions on young people’s mental health in the UK but to date, these data have been largely quantitative. The aim of the current study was to gain a deeper understanding of young people’s experiences in relation to their mental health and wellbeing during the pandemic. Seventeen young people, aged 11 to 16 years, sampled for diverse characteristics, and living in the UK, were interviewed virtually between December 2020 and February 2021. Reflexive thematic analysis was carried out by the research team, which included two young people, and five themes were developed: (1) positives; (2) worries and anxiety; (3) sadness and anger about losses; (4) mental exhaustion; and (5) support from others. Aspects of young people’s individual circumstances (e.g., pre-existing mental health difficulties; special educational needs and neurodevelopmental disorders) appeared to play a role in their experiences. Continued measurement of young people’s mental health, initiatives to identify young people who have been struggling and the provision of support (including evidence-based and accessible interventions) will be important for protecting young people from future adversities as we emerge from the pandemic.